Increasing Values of the Lateral Talar-First Metatarsal Angle Preoperatively Predict Spring Ligament Attenuation in Adult Acquired Flat Foot Deformity. Issue 4 (16th October 2019) - Pate, Matthew; Hall, Jacob; Albright, Patrick; Bohay, Donald; Anderson, John; Roberts, Justin
Category: Ankle, Hindfoot, Trauma Introduction/Purpose: Adult acquired flat foot deformity (AAFD) is responsible for numerous adult foot and ankle deformities, and spring ligament damage has been implicated in the pathology of AAFD. Treatment of AAFD may involve attempts to address spring ligament incompetency, and preoperative knowledge of spring ligament integrity would be valuable in planning for such procedures. To our knowledge, there have been no attempts to correlate preoperative radiographs with direct intraoperative evaluation of spring ligament competency. This study aims to examine the relationship between preoperative radiographic measures specific to flatfoot deformity and intraoperative competency of the spring ligament during flatfoot reconstruction in order to find radiographic measures predicting spring ligament attenuation. Methods: The operative reports of 3 fellowship trained orthopaedic foot and ankle surgeons were searched over a 5-year period from 2012-2017. Patients with pre-operative standing AP and lateral radiographs along with an operative report directly visualizing and commenting on spring ligament integrity were included in the study. Investigators reviewed operative reports to identify patients with spring ligament tears and evaluated pre-operative radiographs. Five common radiographic parameters were measured: lateral talar-first metatarsal angle, AP talar-first metatarsal angle, talonavicular coverage angle, talonavicular coverage percentage, and calcaneal pitch. Chi-square and logistic regression analysis were used to evaluate the five radiographic parameters for association with spring ligament tear. Results: The study enrolled 58 patients with 29 patients having confirmed spring ligament tears and 29 patients having an intact spring ligament. Increasing values for each of the 5 radiographic measures were statistically significant predictors for spring ligament tear on univariate analysis (p=0.001) with the lateral talar-first metatarsal angle being the most significant predictor for spring ligament tear (p<0.001). On logistic regression analaysis, LT-1st angle was a significant predictor of spring ligament tear (p<0.001). A lateral talar-first metatarsal angle =30 degrees had a sensitivity and specificity of 65% and 100% for spring ligament attenuation. The positive predictive value of spring ligament tear with a lateral talar-first metatarsal angle =30 degrees was 100% and the negative predictive value was 74%. Conclusion: This study is the first to correlate preoperative radiographs with direct visualization and evaluation of spring ligament competency. Increasing severity of common radiographic measures of flat foot deformity, particularly the lateral talar-first metatarsal angle, correlate significantly with spring ligament tear and may assist surgeons in planning appropriate preoperative interventions.